Cardiometabolic disorders and menopausal hormone therapy - V Ye Balan; L M Ilina; E V Tikhomirova; A V Tsarkova; I N Lazareva; D V Grigorieva (IP Berlin A.V., 2017)
The review highlights the role of endo- and exogenous estrogens and androgens in the genesis of cardiometabolic disorders in postmenopausal women and the role of menopausal hormone therapy in their prevention.